Sistem Informasi Pengelolaan Data Inventarisasi Barang Pada Kantor Kecamatan Dusun Utara Kabupaten Barito Selatan - Agung Prabowo; Arliyana Arliyana; Jhonyver Jhonyver (Jurnal Sains Komputer dan Teknologi Informasi, 2022)
The data collection of inventory items carried out at the North Dusun District Office in South Barito Regency uses the Microsoft Word application in the Microsoft Office application. Data collection in this way takes a lot of time when making reports when needed. With the existence of these problems, the writer will discuss them in this final project research. By taking the title "Goods Inventory Data Processing Information System in North Dusun District, South Barito Regency". With the hope that the application will provide answers to the solution in processing data to obtain the desired information, especially in processing goods inventory in North Dusun District with Microsoft ® Visual Basic .NET2010 Ultimate and MySQL as a database. The methodology used in making this application is a waterfall. The programming language is Microsoft ® Visual Basic .NET 2010 Ultimate. The database uses MySQL. Tools and Editor used are XAMPP for windows. The methods used in data collection such as interviews, observations, documentation of study literature and experiments The system is expected to help the process of managing inventory data of KIB A, KIB B, KIB C and reports. From the results of the questionnaire with the Likert Scale method, the writer can conclude about the user's opinion regarding the application made, that the user is satisfied with the display design and presentation of the information presented. the results of the questionnaire that have been calculated using the Likert scale method, the Likert scale results are 84.2% or 337 point values included in the interval category Setuju (S).